I vinden, med maskinen: Kulturanalyser av sport - Jönsson, Lars-Eric (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2011)
Sailing and cycling deliver different opportunities to study sport practices. In this article cycling is focused as one way of expressing the relation between man and machine. In no other sport is this connection, or even amalgamation, between the human being and the tool better expressed. Competetive cycling and sailing also generate interesting possibilities to study individuality versus collectivity. The article argues for a study of these and such sporting practices with the aim to understand sport itself and its productive relation to society.